Labour Resilience and Vulnerable Groups in Times of Crisis: A Comparative Study in Eleven European Countries (European Journal of Marketing and Economics, 2023)
The financial crisis which hit the world economies in 2008 has had a negative effect across the spectrum of European economies. These impacts have been felt through the fall in economic activity and also by the deterioration of the labour market indicators. However, not all European markets have been hit with the same severity and intensity, causing territorial differences. But, beyond this, the crisis has had a clear impact on the labour force by exacerbating work inequality. Consequently, the concept of labour emerges through the adaptation of labour markets and the different results obtained amongst the collectives who make up the labour force. The present research has the dual goal of both describing and comparing the labour shock caused by the economic crisis in eleven European countries, establishing differences in employment outcomes of youth (15-24yrs of age), older (55-64yrs of age) and migrants workers by comparing key labour market indicators obtained from official statistical sources. Moreover, it reveals a documented analysis of various national reports describing the employment position of these groups. The results show similarities in the labour vulnerability patterns among countries in each of the groups studied. The analysis highlights the existence of certain factors linked to labour resilience of each group including economic, social, occupational, demographic and political factors. The results of this research are under the INSPIRES project, which has been funded by the Seventh Framework Programme of the European Commission.
Keywords: Labour market, financial crisis, unemployment, resilience, vulnerable groups